Gas Gangrene as a Result of Femoral Traction Pin Placement - Benjamin C. Taylor; Thomas J. Bramwell; Nathan Formaini (Case Reports in Orthopedics)
Treatment of adult femoral shaft fractures typically involves operative stabilization with intramedullary implants, external fixation, or a plate and screw construct. However, when stabilization is delayed for any reason, use of a traction pin is recommended to stabilize the fracture, prevent significant shortening, as well as to help with pain control. In this paper, we present the rare complication of a severe gas gangrene infection caused by Clostridium perfringens that led to several amputations and ultimately death. We also discuss risks of temporary skeletal traction and techniques to overcome the morbidity of such a procedure.